The phenotype associated with a large deletion on MECP2 - Bebbington, A.; Downs, Jennepher; Percy, A.; Pineda, M.; Zeev, B.; Bahi-Buisson, N.; Leonard, H. (Nature Publishing Group, 2012)
Multiplex ligation-dependent Probe Amplification (MLPA) has become available for the detection of a large deletion on the MECP2 gene allowing genetic confirmation of previously unconfirmed cases of clinical Rett syndrome. This study describes the phenotype of those with a large deletion and compares with those with other pathogenic MECP2 mutations. Individuals were ascertained from the Australian Rett Syndrome and InterRett databases with data sourced from family and clinician questionnaires, and two case studies were constructed from the longitudinal Australian data. Regression and survival analysis were used to compare severity and age of onset of symptoms in those with and without a large deletion. Data were available for 974 individuals including 51 with a large deletion and ages ranged from 1 year 4 months to 49 years (median 9 years). Those with a large deletion were more severely affected than those with other mutation types. Specifically, individuals with large deletions were less likely to have learned to walk (OR 0.42, 95% CI: 0.22–0.79, P=0.007) and to be currently walking (OR 0.53, 95% CI: 0.26–1.10, P=0.089), and were at higher odds of being in the most severe category of gross motor function (OR 1.84, 95% CI: 0.98–3.48, P=0.057) and epilepsy (OR 2.72, 95% CI: 1.38–5.37, P=0.004). They also developed epilepsy, scoliosis, hand stereotypies and abnormal breathing patterns at an earlier age. We have described the disorder profile associated with a large deletion from the largest sample to date and have found that the phenotype is severe with motor skills particularly affected.